2013
DOI: 10.1200/jco.2013.50.5511
|View full text |Cite
|
Sign up to set email alerts
|

Interim Cosmetic and Toxicity Results From RAPID: A Randomized Trial of Accelerated Partial Breast Irradiation Using Three-Dimensional Conformal External Beam Radiation Therapy

Abstract: 3D-CRT APBI increased rates of adverse cosmesis and late radiation toxicity compared with standard WBI. Clinicians and patients are cautioned against the use of 3D-CRT APBI outside the context of a controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(234 citation statements)
references
References 31 publications
8
218
2
6
Order By: Relevance
“…4 In each trial, roughly 90% or more of enrolled patients had T1, N0 and hormone-sensitive disease. Data from other large randomized phase 3 trials evaluating APBI, including the National Surgical Adjuvant Breast and Bowel Project B39/Radiation Therapy Oncology Group (RTOG) 0413 trial 5 and Randomized Trial of Accelerated Partial Breast Irradiation trials, 6 are pending.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In each trial, roughly 90% or more of enrolled patients had T1, N0 and hormone-sensitive disease. Data from other large randomized phase 3 trials evaluating APBI, including the National Surgical Adjuvant Breast and Bowel Project B39/Radiation Therapy Oncology Group (RTOG) 0413 trial 5 and Randomized Trial of Accelerated Partial Breast Irradiation trials, 6 are pending.…”
Section: Resultsmentioning
confidence: 99%
“…Most important, the Randomized Trial of Accelerated Partial Breast Irradiation trial randomized 2135 patients to WBI or 3D-CRT APBI. 6 Although the IBTR risk has not yet been reported, cosmetic outcome, as assessed separately by patients, nurses, and physician panels, was consistently worse at 3 and 5 years in patients randomized to 3D-CRT APBI. 15 In contrast, the University Florence phase 3 trial reported that IMRT APBI resulted in improved physician-rated cosmetic outcome compared with WBI.…”
Section: Comment On External Beam Apbimentioning
confidence: 93%
“…Twenty-one percent of patients treated with APBR using IMRT, 38.5 Gy in 3.85 Gy fractions twice daily, at the University of Michigan developed unacceptable adverse cosmesis, leading to early closure of the trial [23]. Excellent or good cosmesis was reported in 73%-82% of patients treated with APBR using 3D-CRT with various fractionation schedule [19,22,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Some initial reports have showed acceptable cosmesis with external beam photon ABPI [50][51][52]. However, a multicenter randomized trial demonstrated increased rates of adverse cosmesis with external beam photon APBI compared with whole breast irradiation [53]. The APBI dose-fractionation regimen in that study remains the most commonly employed regimen in North America.…”
Section: Clinical Applications For Pbt In Breast Cancermentioning
confidence: 96%